Environmental impact assessment: theory, practice and implications for Mekong hydropower debate - Campbell, Lauren; Suhardiman, Diana; Giordano, Mark; McCornick, Peter G. (Baltzer Science Publishers, 2016)
Hydropower development in the Lower Mekong Basin is occurring at a rapid pace. With partial funding from international financial institutions has come pressure on the riparian governments to ensure that the potential environmental and social impacts of hydropower projects are properly considered. Environmental Impact Assessment (EIA) is one of the primary environmental management tools being proposed to fulfill these obligations. This article highlights some of the challenges that are inherent in applying EIA in the Mekong context through critical analysis of both its conceptual and institutional aspects. The main argument of the article is that while EIA application indicates a certain degree of environmental consideration, it is not necessarily sufficient to ensure good environmental practices. Lending institutions such as the World Bank have identified lack of implementation capacity as the biggest constraint to effective EIAs. Focusing on Laos, we show how EIA application should be equipped with necessary institutional arrangements and a transparent public participation process. This will ultimately require a shift within the region to allow environmental and social issues to be given significant weight.